Introduction: Memory, Truth, and Reconciliation in the Wake of Human Brutality - Hollander, Aaron T. (Journal of ecumenical studies, 2025)
This essay introduces the seven articles originally presented at the 2024 annual conference of the North American Academy of Ecumenists in Toronto, Ontario, September 27–29, 2024, pertaining above all to the Canadian Truth and Reconciliation Commission (TRC), to analogous processes of reckoning with Christian complicity in Indigenous abuse, marginalization, and genocide, and to broader areas of inquiry in which “memory,” “truth,” and “reconciliation” name indispensable dimensions of interconfessional conflict and coexistence.